Energetic Behavior Study in Phase Transformations of High Temperature Cu-Al-X (X: Mn, Te, Sn, Hf) Shape Memory Alloys - Canbay, Canan Aksu; Karaduman, Oktay; Unlu, Nihan; Ozkul, Iskender; Cicek, Mehmet Ali (Springer India, 2021)
Shape memory alloys (SMAs) are increasingly used in a wide range of thermomechanical and thermoelectric applications that are of a macro-, micro- and nano-scale. Though the use of commercial Ni-Ti (NiTiNOL) SMAs is preferred in most of these applications, there is an ever-increasing demand for cost-effective and easy-to-produce alternatives to NiTiNOL. In terms of functional properties, copper-based SMAs are comparable to Ni-Ti SMAs. Moreover, Cu-based SMAs are cheaper and easier to produce and process. In order to improve the functional properties of binary Cu-based SMAs (Cu-Al, Cu-Zn and Cu-Sn), ternary elements are added in small quantities. This is also one of the most common methods that is used to improve the functional properties of NiTi- and Fe-based SMAs. In this work, Cu-Al-based alloys containing ternary elements, Mn, Sn, Te and Hf, were produced by arc melting technique. Thermal (DSC, DTA) and microstructural (XRD, metallography) analyses were then carried out on the alloys prepared so as to characterize them for their thermal and microstructural characteristics. The results demonstrate improved shape memory properties for these alloys. The transformation temperatures of the binary Cu-Al alloys determined showed higher values (A(f) > 100 degrees C). Among the ternary alloys, the highest transformation temperatures were found for alloys with Hf addition, followed by those with Te addition. But on the other hand, the most intense peaks corresponding to the martensitic transformation were observed for Sn addition. The microstructural investigations revealed the presence of martensite in the alloys which was consistent with the results of thermal analysis.
Keywords: Hf-doped Cu-based HTSMAs; Cu– Al– Hf; Cu– Al– Sn; Martensite; Austenite; DSC; DTA